2017
DOI: 10.1007/s11481-017-9749-2
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Innate Immunity: a Review

Abstract: Dopamine (DA) is a neurotransmitter in the central nervous system as well as in peripheral tissues. Emerging evidence however points to DA also as a key transmitter between the nervous system and the immune system as well as a mediator produced and released by immune cells themselves. Dopaminergic pathways have received so far extensive attention in the adaptive branch of the immune system, where they play a role in health and disease such as multiple sclerosis, rheumatoid arthritis, cancer, and Parkinson's di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 281 publications
4
88
0
2
Order By: Relevance
“…Microglia are major mediators in the immune response to CNS infection or tissue damage releasing a variety of cytokines upon activation (Mack et al, 2003; Davalos et al, 2005; Saijo, Crotti and Glass, 2013; Nayak et al, 2014). Their dysregulation has been implicated with many neurodegenerative diseases (Pinoli et al, 2017). …”
Section: Dopamine Regulation Of the Peripheral Immune Systemmentioning
confidence: 99%
“…Microglia are major mediators in the immune response to CNS infection or tissue damage releasing a variety of cytokines upon activation (Mack et al, 2003; Davalos et al, 2005; Saijo, Crotti and Glass, 2013; Nayak et al, 2014). Their dysregulation has been implicated with many neurodegenerative diseases (Pinoli et al, 2017). …”
Section: Dopamine Regulation Of the Peripheral Immune Systemmentioning
confidence: 99%
“…Most recently described IBD susceptibility genes are linked to host immune system including epithelial barrier function, host defence mechanisms against pathogens as well as autophagy, innate and adaptive immune response [29]. IBD is characterized by upregulation of proinflammatory cytokines (TNF-α, interleukin (IL)-6, IL-13, IL-17, IL-18, and IL-21) and decrease of anti-inflammatory cytokines (IL-10, IL-11, and transforming growth factor β) [30].…”
Section: Resultsmentioning
confidence: 99%
“…Mononuclear phagocytes are also critical in tissue restoration after injury, as well as in the initiation and resolution of innate and adaptive immune responses [30]. DA and dopaminergic agents can affect several functions of monocytes; for example, DA is able to decrease LPS-induced proliferation of human monocytes [37].…”
Section: Fig 2 Clinical and Macroscopic Features Of Iodoacetamide-imentioning
confidence: 99%
“…Although dopamine is known for its role as a neurotransmitter, it has been described that this mediator can also modulate the immune response [1]. Cells of the cutaneous immune system express dopaminergic and ARs.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine is a key neurotransmitter connecting the nervous and the immune systems as well as a mediator produced and released by immune cells [1, 2]. It has been demonstrated that dopamine and catecholamines, adrenaline and noradrenaline, modulate proliferation, apoptosis, and cytokine production in immune cells [3, 4].…”
Section: Introductionmentioning
confidence: 99%